Viscosity reduction of extra heavy crude oil by magnetite nanoparticle-based ferrofluids - Juan E Aristizábal-Fontal; Farid B Cortés; Camilo A Franco (Adsorption Science & Technology)
The main objective of this work is to synthesize and evaluate magnetite (Fe 3 O 4 ) nanoparticle-based ferrofluids for reducing the viscosity of an extra heavy crude oil. The carrier fluid of the nanoparticles was synthesized using an engine lubricant recycled from the automotive industry and hexadecyltrimethylammonium bromide as a surfactant. Fe 3 O 4 nanoparticles were synthesized by coprecipitation method. The effect of the concentration of nanoparticles in the viscosity reduction degree was determined for dosages between 0 and 50,000 mg/L. Different dosages of carrier fluid were evaluated between 0 and 10% v/v. The effects of the amount of brine emulsified, temperature, time, and shear rate were assessed. Overall, the results showed that viscosity and shear stress of extra heavy crude oil could be reduced up to 81 and 78% in the presence of ferrofluid, respectively. The rheological behavior of extra heavy crude oil in the presence and absence of ferrofluid was assessed by Cross, Ostwald-de Waele, and Herschel-Bulkley models.